KONSEP TASAWUF SYEKH MUHAMMAD ARSYAD AL-BANJARI - Nuraida Nuraida (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
Shaykh Muhammad al - Banjari Arsyad , derived from Banjar South Kalimantan . He was a well-known figure in the 18th century. His role was not only in education , but he was known as a great scholar of fiqh and also an expert in field of Sufism . This had been the result obtained for about thirty years studying in Mecca . Therefore , he was recognized as one of the transmission of the Middle East teaching, particularly in Banjar Indonesia South Kalimantan . His study of Sufism was written in “Kanz al Ma'rifah” . In this book, Ma'rifah is not separated from the concept of knowing God and ourselves . If someone recognizes him, he should recognize his god. Knowing God means knowing the origin of human, aacording to Arsyad, it is called Nur Muhammad ; mortal before death.